Studies On In Vitro Morphogenetic Potential Of Nodal Segments Of Malaxis Acuminata D. Don (Applied Biological Research, 2012)
Malaxis acuminata is a therapeutically important terrestrial orchid.  Due to various anthropogenic activities and over-collection for  medicinal purposes the species is under threat in its natural habitat. A  successful attempt was made to propagate this species using nodal  segments from axenic source as alternative explants. Invocation of  meristematic loci from the cultured nodal segments initiated within  three weeks of culture on MS medium fortified with sucrose (3%,  w/v), NAA and BA (3 µM each in combination). Under this condition  as many as 18 shoot buds developed. The resultant shoot buds converted into plantlets with well developed roots on MS medium  supplemented with sucrose (3%), NAA and BA (3 µM each in  combination) where average plant height and number of leaves,  shoots and roots were 2.4 cm, 4.5, 18.0 and 4.0, respectively. The hardened regenerates were transferred to community potting mix  prepared by mixing charcoal pieces, chopped forest litter, coconut  husk, sand and black soil in equal proportion. About 75% of  transplants survived after 2 months of transfer.
Keywords: Malaxis acuminata; medicinal orchid; micro propagation; nodal explants